Serum anti-Müllerian hormone concentration and follicle density throughout reproductive life and in different diseases—implications in fertility preservation. Issue 12 (29th November 2019) - Liebenthron, J; Reinsberg, J; van der Ven, K; Saenger, N; Kruessel, J-S; von Wolff, M
Abstract: STUDY QUESTION: How do anti-Müllerian hormone (AMH) serum concentrations and follicle densities (FDs) change with age and disease and what are the implications for fertility preservation? SUMMARY ANSWER: AMH concentrations and FD do not correlate in young women, and AMH but not FD is reduced in some diseases, limiting the value of AMH as a predictive parameter of ovarian tissue transplantation. WHAT IS KNOWN ALREADY: AMH is widely used as a parameter to estimate the ovarian reserve. However, the reliability of AMH to predict total number of follicles and the FD is questionable. Women with lymphoma and leukaemia have been shown to have reduced AMH concentrations, but it is unknown if the FD is also reduced. In fertility preservation it is essential to estimate the correct total number of follicles and the FD, as ovarian tissue should only be cryopreserved if ovarian reserve is high. Furthermore, the amount of tissue to be transplanted should be based on the estimation of the real FD. STUDY DESIGN, SIZE, DURATION: This retrospective observational study included 830 women (mean ± SD age, 28.2 ± 6.81 years; range, 4–43 years) with malignant ( n  = 806) and benign ( n  = 24) diseases who cryopreserved tissue in a single centre as part of a national fertility preservation programme. Females with ovarian surgery or known predispositions for a reduced ovarian reserve were excluded. AMH concentrations and FD were evaluated from March 2011 to September 2016. PARTICIPANTS/MATERIALS, SETTING, METHODS: AMH concentrations were analysed before gonadotoxic therapies. Standardized biopsies, obtained from different areas of ovarian cortex, were collected. FD was analysed after tissue digestion and calcein staining and was expressed as average number of primordial and primary follicles count per 3 mm biopsy and per cubic millimeter tissue. AMH concentrations and FD were analysed in relation to age and diagnosis group. Both parameters were age adjusted, and associations between the different diagnosis groups and AMH versus FD were assessed. MAIN RESULTS AND THE ROLE OF CHANCE: Mean ± SD AMH concentration was 3.1 ± 2.81 g/ml, mean FD per 3 mm biopsy was 137 ± 173.9 and 19.4 ± 24.60 per mm 3 . Maximum AMH concentrations were found in children and teenagers at the age of 6–10 years (5.71 ng/ml) and in adults at the age of 21–25 years (3.33 ng/ml). FD was highest in young children up to an age of 15 years and decreased with increasing age. AMH and FD were not correlated in women ≤20 years and weakly to moderately correlated in women 21–40 years ( r  = 0.24–0.39). Age-adjusted correlations between AMH and FD were demonstrated in several diagnosis groups such as breast cancer, leukaemia, sarcoma, gastrointestinal cancer and gynaecological cancer but not in the groups exhibiting Hodgkin's and non-Hodgkin's lymphoma, cerebral cancer, other types of malignancies and other types of benign diseases. Further statistical analysis supported the finding that, in some diagnosis groups such as Hodgkin's lymphoma and in gynaecological cancer, AMH concentrations but not FDs are reduced, questioning the prognostic accuracy of AMH for the FD in these diseases. LIMITATIONS, REASONS FOR CAUTION: Even though biopsies were taken from different sites, heterogenous distribution of follicles might have had some effect on the accuracy of the analysis. WIDER IMPLICATION OF THE FINDINGS: AMH should be used with care to estimate the total ovarian reserve and FD of cancer patients in young women in some diseases. Therefore, calculating the amount of ovarian tissue to be transplanted based solely on AMH might be inaccurate whereas FD might be a better parameter. STUDY FUNDING/COMPETING INTEREST(S): The study did not receive any exterior funding.